Kepemimpinan Karismatik dalam Membangun Mutu Performa Guru Pendidikan di Madrasah Diniyah - Abdul Wahid; Tariman Tariman; Hefniy Hefniy (Universitas Nurul Jadid, 2021)
Abstract: The existence of this paper is to analyze the leadership of the kiai figure in building the quality of the performance of formal diniyah education teachers at the Nurul Qodim Islamic Boarding School. This study uses a qualitative approach to examine the condition of natural objects. The data collection techniques used were interviews, observation and document studies which are directly related to the characteristics of KH's charismatic leadership. Nuruddin Musyiri and KH. Hasan Abdul Jalal at the Nurul Qadim Islamic Boarding School Kalikajar kulon Probolinggo. The focus of this research is how is charismatic leadership in building the quality of the performance of Ulya Nurul Qadim Probolinggo formal diniyah education teachers? Charismatic leadership can be the right choice in improving teacher performance. The results of his research show that charismatic leadership at the Nurul Qadim Islamic Boarding School is leadership that promotes exemplary caregivers, character building, improving the quality of education, evaluating as a whole, and having the spirit of Al-Jihad spirit, and remaining patient.